'Mud in my ears and jam in my beard': Challenging gendered ways of being in nature kindergarten practitioners. Issue 2 (3rd April 2019) - Nugent, Clare; MacQuarrie, Sarah; Beames, Simon
ABSTRACT: Nature kindergartens present opportunities to foster a love of natural environments through formative early childhood experiences. Three early childhood education settings – one in Denmark, one in Finland and one in Scotland – provided insight into nature kindergarten provision that has historically attracted a high proportion of male staff. At the three cases, this qualitative study recorded observation and interview data during 53 sessions across 16 months, with each setting being visited once in each season. Work by Foucault [1976. "Truth and Power." In Essential Works of Foucault, edited by P. Rabinow, 111–133. New York: The New Press; Foucault. 1978. The History of Sexuality . Volume I. New York: Vintage] and Connell [2005. Masculinities . Cambridge: Policy Press] permit a deeper understanding of the ways in which different environments may afford specific kinds of social interaction that privilege certain 'ways of being'. This paper provides a nuanced consideration of how masculinities and femininities, shaped through governing socio-cultural discourses, are evident in nature kindergarten practice. The findings feature descriptions of simple, quotidian practices that have local relevance to each setting and were recognised to support nature-based learning. Such practices are influenced by practitioner-held, gendered dispositions and orientations towards nature that collectively underpin career choice and sustain contributions to the early childhood education workforce. This research adds to the developing literature regarding nature kindergartens, nature-based learning and early-childhood education and offers suggested directions for future research.